The Role of Teachers in Enhancing Early Childhood Self-Confidence Through Project-Based Learning: A Study at Gaussian Kamil School Semarang - Riana Aprilianti (Universitas Negeri Semarang, 2026)
This study examines the role of teachers in enhancing self-confidence among early childhood learners through project-based learning at Gaussian Kamil School Semarang. A qualitative descriptive method was used in this study. The participants of this study were teachers, the school principal and students from Kindergarten B at Gaussian Kamil School Semarang. Data were collected by means of observation, interviews and analysis of documents. The data were analyzed by using an interactive data analysis model, namely reduction, display, and conclusion drawing. The results of this study revealed that teachers played crucial roles of facilitators, motivators, and guides of students in their learning processes. How teachers organized students collaborative learning, assigned each child with roles in the project, encouraged students to present their work, and allowed students to explore their ideas by using loose parts, helped students to recognize their strengths and to be confident in their learning processes. students who were involved in project-based learning also developed their communication skills, critical thinking, and independence. Therefore, project-based learning provided students with meaningful opportunities to develop their self-confidence through their active involvement in learning processes and authentic learning experiences. Teachers played important roles in constructing learning environments where students felt valued, heard, and supported, and in which students self-confidence could be developed alongside other aspects of child development.